C♯ and VB .NET conversion pocket reference - Mojica, Jose (O'Reilly, 2002)
Though most programmers use two or more languages, they usually have a mastery of one. Although Microsoft has advertised that the .NET runtime is language agnostic and that C♯ and Visual Basic .NET are so close that switching between the two is really quite easy, that?s only true up to a point. Some of the differences are obvious, but others are very subtle. C♯ & VB.NET Conversion Pocket Reference helps you easily make the switch from one language to another. The differences occur in three main areas: syntax, object-oriented principles, and the Visual Studio .NET IDE. Syntax concerns the s.